Can polychlorinated biphenyl (PCB) signatures and enantiomer fractions be used for source identification and to age date occupational exposure?. (August 2015) - Megson, David; Focant, Jean-Françios; Patterson, Donald G.; Robson, Matthew; Lohan, Maeve C.; Worsfold, Paul J.; Comber, Sean; Kalin, Robert; Reiner, Eric; O'Sullivan, Gwen
Abstract: Detailed polychlorinated biphenyl (PCB) signatures and chiral Enantiomer Fractions (EFs) of CB-95, CB-136 and CB-149 were measured for 30 workers at a transformer dismantling plant. This was undertaken to identify sources of exposure and investigate changes to the PCB signature and EFs over different exposure periods. Approximately 1.5 g of serum was extracted and PCB signatures were created through analysis by comprehensive two-dimensional gas chromatography with time-of-flight mass spectrometry (GC × GC–TOFMS) and EFs calculated following analysis by gas chromatography with high resolution mass spectrometry (GC–HRMS). A total of 84 PCBs were identified in the serum samples with concentrations of the 7 indicator PCBs ranging from 11–350 ng g − 1 of serum (1.2–39 μg g − 1 lipid). The PCB signatures were interpreted using principal component analysis (PCA) which was able to distinguish workers with background or recent minimal exposure from those with prolonged occupational exposure. Occupationally exposed individuals had a similar PCB profile to Aroclor A1260. However, individuals with prolonged exposure had depleted proportions of several PCB congeners that are susceptible to metabolism (CB-95, CB-101 and CB-151) and elevated proportions of PCBs that are resistant to metabolism (CB-74, CB-153, CB-138 and CB-180). The results also identified a third group of workers with elevated proportions of CB-28, CB-60, CB-66, CB-74, CB-105 and CB-118 who appeared to have been exposed to an additional source of PCBs. The results show near complete removal of the CB-95 E2 enantiomer in some samples, indicating that bioselective metabolism or preferential excretion of one enantiomer occurs in humans. By considering PCB concentrations along with detailed congener specific signatures it was possible to identify different exposure sources, and gain an insight into both the magnitude and duration of exposure. Graphical abstract: Highlights: Eighty four different PCBs detected in human serum samples PCB signatures used to distinguish recent and prolonged exposure PCB signatures used to identify different sources of exposure Near complete removal of the CB-95 E2 enantiomer recorded in some humans